Surprises from Telephone Deregulation and the AT&T Divestiture - Crandall, Robert W. (American Economic Review, 1988)
Undoubtedly, the greatest surprise in telephone industry deregulation has been the absence of deregulation, for the industry continues to be almost as highly regulated today as twenty years ago. Entry has been greatly liberalized in the equipment and most services markets, AT&T has been broken up, but the most important intrastate and interstate telephone services continue to be subject to formal rate regulation. Competitive entry has made this regulation more difficult, not politically less compelling. The major event in the telephone industry has not been deregulation, but divestiture. In 1984, AT&T was divested of its operating companies as the result of an historic 1982 antitrust decree. In this paper, I summarize some of the early effects of divestiture, including: (i) the virulence of the politics to keep the uneconomic subsidies that invited competitive entry in the first place, (ii) the preliminary evidence that AT&T is losing by winning and not vice versa, (iii) the new competition in equipment markets that may turn out to be more important than the recent developments in services competition, (iv) the misplaced concerns about the loss of system efficiency and service quality due to divestiture, and (v) the plight of the divested regional Bell holding companies (RBOCs).